2013
DOI: 10.1111/jopy.12001
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Prosociality from Adolescence to Early Adulthood: The Role of Effortful Control

Abstract: Being able to regulate one's own emotions and behaviors in early adolescence may not only affect the tendency to behave prosocially, but also counter the self-centered tendencies observed across this phase of development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
75
1
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 74 publications
12
75
1
7
Order By: Relevance
“…Kochanska et al (1997) show strong links between IC and multiple, diverse measures of children's conscience at early school age, including observations of moral conduct, moral cognition, and moral self in toddler and early school age. The present result that EfC seems to suppress Ego is consistent with the result of Luengo Kanacri et al (2013).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Kochanska et al (1997) show strong links between IC and multiple, diverse measures of children's conscience at early school age, including observations of moral conduct, moral cognition, and moral self in toddler and early school age. The present result that EfC seems to suppress Ego is consistent with the result of Luengo Kanacri et al (2013).…”
Section: Discussionsupporting
confidence: 93%
“…EfC is associated with the development of the prefrontal cortex (e.g., Gulley et al, 2016). It is reported that EfC-being able to regulate one's own emotions and behaviors-in early adolescence may positively influence one's prosocial behavior and negatively affect the self-centered tendencies observed in adolescence (Luengo Kanacri et al, 2013).…”
mentioning
confidence: 99%
“…Moreover, women also had a more positive quadratic trajectory and caught up with men’s levels of community service by age 26. The reasons for these different patterns are unclear, but these results conflict with closely related research on prosocial behavior showing females start and remain higher on prosocial behavior across young adulthood (Luengo Kanacri et al, 2013). Youth who reported no college plans experienced less decline than average after high school; this pattern is unexpected based on prior research, but could be due to the low starting level at age 18.…”
Section: Discussioncontrasting
confidence: 74%
“…Insofar as successive cohorts of youth increasingly experience delay in social roles, this pattern should be particularly true for more recent cohorts. The expected curvilinear pattern of decline with subsequent increase in young adulthood has been found with social trust and prosociality (Jennings & Stoker, 2004; Luengo Kanacri et al, 2013), which are associated with community service. This pattern may be particularly true for recent cohorts, who experience more delays in social roles (Settersten & Ray, 2010).…”
Section: Community Service During the Transition To Adulthoodmentioning
confidence: 95%
“…For example, by inhibiting a dominant, maladaptive response to harm done (e.g., avoidance), children may activate a subdominant, adaptive response (reparation in this case; see Eisenberg, 2005). However, despite numerous studies linking effortful control to prosocial behavior in general (e.g., Diener & Kim, 2004;Eisenberg et al, 1996;Kochanska, Barry, Jimenez, Hollatz, & Woodard, 2009;Luengo Kanacri, Pastorelli, Eisenberg, Zuffianò, & Caprara, 2013), only one study to date has documented a positive relation between inhibitory control and reparation in early childhood (see Kochanska et al, 1994). In this cross-sectional study, Kochanska and colleagues (1994) collected maternal and paternal reports of 171 21-to 70-month-old children and found that inhibitory control was positively associated with reparation after wrongdoing.…”
Section: Inhibitory Control and Reparative Behaviormentioning
confidence: 99%